(untitled) (The Review of Diabetic Studies, 2025)
The research aims to assess the orthodontic treatment on facial aesthetics and symmetry in 100 patients. There were 75 women and 25 men. A quantize research method was chosen, and data were collected concerning the types of malocclusions, procedures used in treatment, and FAR both before and after the treatment. Class II malocclusion was the most common type of malocclusion amongst patients. Various orthodontic treatments were performed, including labial, lingual, and invisible braces, with labial treatment being the most common. A statistical analysis showed significant increases in FAR concerning frontal, profile, and overall photo types, thus resulting in an aesthetically improved facial appearance after treatment. Females benefited remarkably in terms of attractiveness, with males achieving consistent and significant gains, although smaller in size.